Gender Violence in the Film Posesif by Gina S. Noer and its Relevance as Indonesian Language Teaching Material - Tiara Anggun Safitri; Ali Imron Al-Ma’ruf (Journal La Sociale, 2024)
Violence against women encompasses any kind of behavior that inflicts physical, sexual, or psychological damage against women. This study investigates the narrative structure of Gina S. Noer's film "Possessive," explores gender-based violence through the lens of feminist studies, and analyzes its significance to Indonesian language education. This research employs a descriptive-qualitative approach. We use an integrated and case study research methodology. This research investigates the film "Possessive" directed by Gina S. Noer, with a specific emphasis on the themes of gender-based violence and narrative structure. This research focuses on the portrayal of gendered violence against women in Gina S. Noer's film "Possessive" and its narrative structure. This inquiry used the film "Possessive" and literary literature. Information was gathered via library research. Data was confirmed using triangulation. Data analysis employs heuristic and hermeneutic approaches to interpret semiotic models. The research revealed that Gina S. Noer's film "Possessive" revolves on themes of love and violence, the narrative structure, the characters of Lala and Yudhis, as well as Lala's domestic and professional environment. Gina S. Noer's film "Possessive" depicts a total of five instances of verbal violence, three instances of psychological violence, three instances of physical violence, and three instances of power-based violence. (3) The findings of this research may be used to develop comprehensive Indonesian language teaching materials for high school students, including language, psychology, and culture.